MORFOLOGI DERIVASIONAL DALAM BAHASA INGGRIS - Sunardi Sunardi (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2012)
Morphological process in English language may occur inflectionally or derivationally. The main difference between inflection and derivation is that inflection does not make a new lexeme but a grammatical word with respect to syntactic rules; however, derivation makes a new lexeme which is lexically different from its base. In English language, derivation may occur through prefixation, suffixation, conversion, and compounding besides other morphological processes such as back formation, reduplication, clipping, acronym, and blending. Â Keywords:derivation, inflection, lexical word, grammatical word, morphological processes